Hormone-mediated growth dynamics of the barley pericarp as revealed by magnetic resonance imaging and transcript profiling - Pielot, Rainer; Kohl, Stefan; Manz, Bertram; Rutten, Twan; Weier, Diana; Tarkowská, Danuše; Rolčík, Jakub; Strnad, Miroslav; Volke, Frank; Weber, Hans; Weschke, Winfriede (Journal of experimental botany, 2015)
The shape of the maternal pericarp affects cereal grain mass and yield. Pericarp growth was analysed by magnetic resonance imaging (MRI), revealing topological maps of mobile water in developing pericarp of barley (Hordeum vulgare) and displaying tissue regions actively elongating in specific temporal-spatial patterns. Correlation analysis of MRI signals and growth rates reveals that growth in length is mediated by dorsal and also lateral rather than ventral regions. Growth in thickness is related to ventral regions. Switching from dorsal to ventral growth is associated with differential expression of axial regulators of the HD-ZipIII and Kanadi/Ettin types, and NPH3 photoreceptors, suggesting light-mediated auxin re-distribution. Auxin increases with the highest levels in the basal pericarp at 6 days after fertilization (DAF), together with transcriptionally up-regulated auxin transport and signalling. Gibberellin biosynthesis is transcriptionally up-regulated only later, and levels of bioactive gibberellins increase from 7 to 13 DAF, with higher levels in ventral than dorsal regions. Differential gene expression related to cell expansion indicates genes related to apoplast acidification, wall relaxation, sugar cleavage, water transport, and cell wall biosynthesis. Candidate genes potentially involved in pericarp extension are distinguished by their temporal expression, representing potential isoforms responsible for dorsal-mediated early growth in length or ventral-mediated late growth in thickness.
Keywords: kyseliny indoloctové; growth dynamics; Magnetic Resonance Imaging; magnetická rezonanční tomografie; directed growth; Hordeum; Plant Growth Regulators; Auxin; barley pericarp; Gibberellins; transcript profiling.; gibereliny; magnetic resonance imaging; regulace genové exprese u rostlin; Gene Expression Regulation, Plant; Gene Expression Regulation, Developmental; Seeds; regulátory růstu rostlin; rostlinné proteiny; gibberellic acid; stanovení celkové genové exprese; Plant Proteins; grain length; ječmen (rod); Indoleacetic Acids; vývojová regulace genové exprese; Gene Expression Profiling; semena rostlinná; cell expansion